2011
DOI: 10.1093/nar/gkr265
|View full text |Cite
|
Sign up to set email alerts
|

Interconversion between bound and free conformations of LexA orchestrates the bacterial SOS response

Abstract: The bacterial SOS response is essential for the maintenance of genomes, and also modulates antibiotic resistance and controls multidrug tolerance in subpopulations of cells known as persisters. In Escherichia coli, the SOS system is controlled by the interplay of the dimeric LexA transcriptional repressor with an inducer, the active RecA filament, which forms at sites of DNA damage and activates LexA for self-cleavage. Our aim was to understand how RecA filament formation at any chromosomal location can induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
81
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 43 publications
(99 reference statements)
8
81
0
3
Order By: Relevance
“…Biochemical analyses showed that only the DNAfree form of LexA is cleaved by activated RecA protein (Butala et al 2011). This study has implications that relate the relative strength of LexA binding sites to the sequential order of induction of genes during the damage response.…”
Section: How Exactly Is Sos Induced?mentioning
confidence: 81%
“…Biochemical analyses showed that only the DNAfree form of LexA is cleaved by activated RecA protein (Butala et al 2011). This study has implications that relate the relative strength of LexA binding sites to the sequential order of induction of genes during the damage response.…”
Section: How Exactly Is Sos Induced?mentioning
confidence: 81%
“…Thus, these two regulators cannot account for the positive effects of CsrA on uvrY transcription. Another candidate is LexA, which coordinates the SOS response (47,48), because a LexA binding site is predicted to be located between nt Ϫ120 and Ϫ139 upstream of the uvrY start site (49). CsrA-dependent modulation of uvrY translation might also be indirect, because no apparent CsrA binding sequences are present in the 5=-UTR of the uvrY transcript.…”
Section: Resultsmentioning
confidence: 99%
“…The SOS gene network is controlled by the LexA repressor, and LexA-regulated genes exhibit heterogeneous expression in a culture not subject to an external SOSinducing treatment . The heterogeneity of expression is a result of stochastic factors resulting from the binding affinity of LexA to different SOS boxes and intrinsic DNA damage (Pennington and Rosenberg 2007;Kamensek et al 2010;Butala et al 2011). Combined heterogeneity of the expression of the target and the repair mechanism translates into a wide spectrum of phenotypic states and hence varied susceptibility to a FQ.…”
mentioning
confidence: 99%